2018
DOI: 10.1186/s12909-018-1415-8
|View full text |Cite
|
Sign up to set email alerts
|

Female dental students’ perceptions of patient safety culture: a cross sectional study at a middle eastern setting

Abstract: BackgroundPatient safety is an integral part of all health care specialties, including dentistry. Dental students are exposed to patient safety culture during their clinical training. The aim of this study was to evaluate the perception of female students enrolled in dental degrees and dental hygiene programs towards patient safety culture and to determine its associated factors at a Middle Eastern setting.MethodsThis is a cross sectional study, based on a self-administered, English language questionnaire dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 37 publications
2
36
0
1
Order By: Relevance
“…Therefore, the questionnaire was reviewed comprehensively from a cultural point of view and the items in the SAQ were evaluated for relevance and acceptance in dental students and interns in Saudi Arabian culture 24 . A recent study in the country used SAQ to assess the underlying concept of patient safety culture amongst dental students 12 . This also supported our cross‐cultural adaptation process 24 .…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, the questionnaire was reviewed comprehensively from a cultural point of view and the items in the SAQ were evaluated for relevance and acceptance in dental students and interns in Saudi Arabian culture 24 . A recent study in the country used SAQ to assess the underlying concept of patient safety culture amongst dental students 12 . This also supported our cross‐cultural adaptation process 24 .…”
Section: Methodsmentioning
confidence: 85%
“…Evidence suggests that the inclusion of patient safety programmes in curricula enables students to recognise the importance of patient safety culture which has positive effects on their healthcare attitudes and behaviours, thus making them safer healthcare providers in the future 12 . Myung et al 13 analysed data of medical students before and after incorporating patient safety course into the curriculum and observed a significant increase in students' awareness about patient safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training is essential for dealing with the problems that professionals may face during their careers 58,59,60 , and it is important to incorporate the theme of patient safety starting in the early years of undergraduate school 61 . One study 39 of Dentistry students identified predisposing human factors related to AE such as operator fatigue, unawareness of risks, and failures of referrals.…”
Section: The Problem's Size and Understanding Its Causesmentioning
confidence: 99%
“…Patient safety culture means the beliefs, values, and standards shared by professionals and that also influence their behaviors and actions 63 . In the course of this review, studies alluded to the theme 13,64,65 or used it as their central focus 47,61,66,67,68,69,70,71,72,73 . Positive points were found, such has a high overall perception of patient safety; patient-centered care; the pursuit of effective and equitable care; and the value assigned to teamwork.…”
Section: The Problem's Size and Understanding Its Causesmentioning
confidence: 99%